Implementation of Safety Culture at the Aviation Security Unit at Betoambari Airport, Baubau City - Muh Taufik Donny Pratama; Walid Jumlad (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Aviation security and safety must be considered in every operation. To prevent accidents, actions that increase safety are needed, such as adopting a safety culture. Safety culture is formed through organizational, professional and national culture that is implemented to maintain flight safety. The aim of this research is to find out how far the safety culture is implemented at the Aviation Security unit at Betoambari Airport. This study uses a research method in the form of a qualitative approach using primary data in the form of interview and observation data and secondary data in the form of literature studies, report data in the form of SOP (Operational Standard) archives related to safety culture and events that have been documented and related to the subject matter. research discussion. Data collection techniques used are observation, interviews and documentation. While the data analysis technique uses data collection, data reduction, data presentation and conclusion. Then in measuring the validity of the researchers used the technique of triangulation of sources and methods. The results of this study looked at the implementation of the safety culture at Betoambari Airport with the implementation of AVSEC officers: performance, work shifts, work coordination, safety briefings with other units according to the SOP in force in the Ministry of Transportation regulation SKEP 2765/XII/ 2010. the obstacles faced by AVSEC officers are related to the need to improve the quality of human resources, coordination with other units such as customs to work optimally and the addition of incomplete facilities to support AVSEC's performance in aviation safety and security.